A fiumei vasút kiépülése és annak város alatti szakasza - Majdán, János (Közép-Európai Közlemények, 2013)
The gaining of a Hungarian railway to the seacoast had been the cause of several serious arguments in the Reform Ages. István Széchenyi had in mind a route that would start from Buda and would connect to the national network, while Lajos Kossuth wished to connect the Danubian port of Vukovar with Fiume. In fact the first railway towards the seacoast and the river Drava on the other side was built with Zagreb as a centre, then the Kelenföld-Baranya-Szentlőrinc route of the Hungarian National Railways – opened in 1882 – secured the direct access. The trains of the Hungarian National Railways travelled on the earlier built section between Dombóvár and Gékényes and on the route between Karlovac (Károlyváros) and Fiume, which reached the seaside docks of the city with the aid of a special tunnel under the town.